Very high temperature tiling of tetraphenylporphyrin on rutile TiO2(110). Issue 32 (4th August 2017) - Lovat, Giacomo; Forrer, Daniel; Abadia, Mikel; Dominguez, Marcos; Casarin, Maurizio; Rogero, Celia; Vittadini, Andrea; Floreano, Luca
Abstract : Self-metalated titanium(iv )-porphyrins with monolayer coverage on TiO2 (110) remain anchored atop the Obr rows across a cyclo-dehydrogenation reaction up to 450 °C. Abstract : We demonstrate the thermal stability up to 450 °C of a titanium(iv )-porphyrin monolayer grown on the rutile TiO2 (110) surface. Starting from a film of metal-free tetra-phenyl-porphyrin, 2HTPP, deposited at room temperature, we show that, beyond the self-metalation reaction at 150°–200 °C, a second phase transition takes place at ∼350 °C. Using surface diffraction and microscopy, we observe a change of the phase symmetry from (2 × 4)- obliq to (2 × 6)- rect . Core level photoemission indicates that the chemical states of both the molecular tetrapyrrolic macrocycle and the substrate are unchanged. X-ray absorption spectroscopy reveals that the driving mechanism is a rotation of the phenyl terminations towards the substrate (flattening) that triggers a conformational change of the molecule through partial cyclo-dehydrogenation. From comparison with first principles calculations, we show that the common feature of these multiple phase transitions is the chemical nature of the porphyrin bonding atop the substrate oxygen rows: the coordination of the macrocycle central pocket to the oxygen atoms beneath is preserved throughout both the self-metalation and flattening reactions. The molecular orientation and arrangement are determined by steric constraints and intermolecular interactions, whereas the specific adsorption site is further stabilized by the interaction of the peripheral C–H network with the adjacent oxygen rows. Porphyrins are thus trapped at the TiO2 (110) surface, where they demonstrate an exceptionally high thermal stability (up to ∼450 °C), which makes this interface potentially useful for sensors and photocatalysis applications in harsh environments.